Práticas pedagógicas remixadas : possibilidades de estratégias docentes alinhadas a tendências emergentes da cultura digital - Martins, Cristina (2020)
This qualitative-descriptive research investigates aspects of teacher education related to emergencies of digital culture. This culture is established in a digital world, where technologies change relationships, conceptions and behaviors of society as a whole and the need for a digital education to understand and act in this new context is pressing. In this scenario, the question that arises (and it is not new) is related to teacher education, specifically with regards to the challenges and possibilities for creating pedagogical practices that address the expectations and training needs of students. Considering this problem, this thesis proposes that teachers should adopt a remixed pedagogical practice, understood as a practice that uses two or more pedagogical strategies based on emerging trends in digital culture. In order to illustrate the operationalization of this proposal, we opted for three strategies: computational thinking, maker culture and gamification, which were called the Contemporary Educational Triad. The theoretical framework of this work is mainly based on reflections by Piaget, Papert and Vygotsky. The idea of remix proposes to combine / mix / transform existing resources and practices to think about the new. In this sense, the main goal of this work is to investigate the contributions to the school ecosystem, when adopting remixed pedagogical strategies, through a case study based on the Contemporary Educational Triad. The research was conducted in two private schools linked to a private education network, located in Porto Alegre / RS. Research subjects were managers of those schools and from the network, teachers and professionals of Educational Technology who work in the places investigated. Data collection instruments consisted of interviews (unstructured and semi-structured) and observations (non-participant with structured). Discursive Textual Analysis was the technique used to support data analysis. At the end of this thesis, the main contributions are to understand the complexity inherent in the establishment of a digital education, whose context is permeated by ubiquity, nonlinearity and the intense change in the way of conducting teaching. It is also highlighted the importance for the teacher to recognize the possibilities offered by the adoption of remixed pedagogical practices aligned with the digital culture, in order to develop a pedagogical project that contemplates the possibility to create / use innovative pedagogical practices, not only from the options available in the school environment, but also from the importance of investment in continuing teacher education. Although the work described does not end with the end of this research, this reflection concludes with the certainty that difference and innovation in teaching and learning situations can be helped by the use of digital technologies, but the decisive element in this process is the teacher who is involved with the necessary background and training to create pedagogical solutions in emerging and challenging contexts that digital world establishes. KEYWORDS: Digital culture. Teacher training. Remixed pedagogical practices. Computational thinking. Maker culture. Gamification.